MODERASI DALAM MEMAKNAI HAK-HAK ANAK - Siti Nurjanah (MODERATIO: Jurnal Moderasi Beragama, 2022)
This paper discusses the concept of moderation inaddressing children's rights in terms of family,environment and society. This paper uses a descriptivequalitative research method that is literary in nature.The result of this paper is to emphasize that there arefour aspects of religious moderation that need to be therights of children in achieving tolerant religiousqualities, namely planting national commitment,strengthening tolerance, anti-violence, and introducingand preserving local culture. Strengthening religiousmoderation is a right to be taught to children from anearly age in the family and community so that childrenare able to have moderate traits and prevent radicalismin the future